2021
DOI: 10.46398/cuestpol.3970.46
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of the organizational and legal mechanism of the Ukrainian state policy in tourism and hospitality

Abstract: The purpose of the work is to analyze the transformation and efficiency of the organizational and legal mechanism of Ukraine's state policy in the field of tourism and hospitality. Methods of grouping, modeling, and forecasting, methods of theorization and historical formalization, as well as methods of analysis, comparison, sampling, and description of the system were used to substantiate scientific principles and approaches for the development of organizational and legal mechanisms of Ukrainian state policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…9 No. 5, 2023 R. Oleksenko, Y. Bortnykov, S. Bilohur, N. Rybalchenko, N. Makovetska (Oleksenko, Bortnykov, Bilohur, Rybalchenko, Makovetska, 2021) presents an analysis of the organisational transformation and effectiveness and legal state policy Ukrainian mechanism in the field of tourism and hospitality, which, from authors' point of view, is important to activate rural green tourism. Thus, the analysis of the literature on the problems of rural green tourism and the study of European practices showed that the effective development of tourism management strategy, including the control of tourist flow and consideration of ecological aspects, is important for the preservation of nature and atmosphere of rural regions.…”
Section: Analysis Of Recent Researches and Publicationsmentioning
confidence: 99%
“…9 No. 5, 2023 R. Oleksenko, Y. Bortnykov, S. Bilohur, N. Rybalchenko, N. Makovetska (Oleksenko, Bortnykov, Bilohur, Rybalchenko, Makovetska, 2021) presents an analysis of the organisational transformation and effectiveness and legal state policy Ukrainian mechanism in the field of tourism and hospitality, which, from authors' point of view, is important to activate rural green tourism. Thus, the analysis of the literature on the problems of rural green tourism and the study of European practices showed that the effective development of tourism management strategy, including the control of tourist flow and consideration of ecological aspects, is important for the preservation of nature and atmosphere of rural regions.…”
Section: Analysis Of Recent Researches and Publicationsmentioning
confidence: 99%